Pemikiran Al-Ghazali dalam filsafat pendidikan Islam: relevansi untuk pendidikan dasar - Nur Hidayat; Yusuf Rendi Wibowo; Fatonah Salfadilah; Mazaya Rahma Maryam (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze Al-Ghazali's thought in Islamic education philosophy and its relevance to contemporary basic education. The research focuses on Al-Ghazali's educational epistemology, its Sufistic-ethical-integrative character, and its practical implications for student character formation. The method used is library research with a philosophical-hermeneutic approach, which involves reading, interpreting, and contextualizing Al-Ghazali's classical texts particularly Iḥyā’ ‘Ulūm al-Dīn and Ayyuhā al-Walad within the framework of modern basic education needs. The findings indicate that Al-Ghazali's thought emphasizes education as a means of moral perfection through the integration of intellect, heart, and behavior. The methods he proposes include role-modeling (uswah), habituation (ta‘wīd), admonition (mau‘iẓah), self-reflection (muhāsabah), and the control of base desires. In the context of contemporary basic education, these ideas are relevant to concepts of character building, reflective education, and holistic learning models, as emphasized in Indonesia's Kurikulum Merdeka (Emancipated Curriculum). However, a limitation of Al-Ghazali's thought is its lack of attention to modern science and technological literacy. Therefore, integrating Al-Ghazali's Sufistic-ethical thought with contemporary pedagogy such as humanistic, constructivist, and holistic education approaches is necessary to develop a basic education model that balances morality, spirituality, and 21st-century competencies.